Half-size modeling of the work of restructured gas-electrical suspension of free gyroscope under conditions of cosmic laboratory - Агарев, В. А. (Proceedings of National Aviation University (archive), 2000)
Having considered the draft of the first stage of experimental research in space the basic principles of building a permanent free gyroscope with adjustable gas-electric rotor suspension. The objectives of the project are: assessment vozmuschayugtsih moments acting on the gyro rotor when the gas in the outer space; optimization of the design parameters of gas-electric tunable suspensions